2014
DOI: 10.1142/s2345768614500299
|View full text |Cite
|
Sign up to set email alerts
|

Game option models of convertible bonds: Determinants of call policies

Abstract: The interaction of bondholder's conversion and issuer's call in a convertible bond leads to a game option model between the two counterparties. Like typical pricing models for corporate debts, the fair value of a convertible bond is highly dependent on issuer's credit risk, tax benefits of coupons and other structural features. The convertible bond pricing models in the literature can be categorized into two approaches: (i) structural firm value models that incorporate dilution effect in the issuer firm's corp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Determinants that were verified to significantly influence the call timings in the literature are controlled. Specifically, increments in coupon rates, decrements in Treasury rate levels, average call prices, Treasury rate volatility, and stock return volatility hasten the call decisions (Bechmann et al, 2014;King & Mauer, 2000, 2014Sarkar, 2003). The signs for the coefficients on these explanatory variables in our regressions are generally consistent with the literature.…”
Section: Links Between Call Timings and The Presence Of Conversion An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Determinants that were verified to significantly influence the call timings in the literature are controlled. Specifically, increments in coupon rates, decrements in Treasury rate levels, average call prices, Treasury rate volatility, and stock return volatility hasten the call decisions (Bechmann et al, 2014;King & Mauer, 2000, 2014Sarkar, 2003). The signs for the coefficients on these explanatory variables in our regressions are generally consistent with the literature.…”
Section: Links Between Call Timings and The Presence Of Conversion An...mentioning
confidence: 99%
“…Though pricing convertibles with default risk can also be handled via Jarrow and Turnbull's (1995) reducedform credit-risk model, such as Chambers and Lu (2007) and Wang and Dai (2017), adopting structural models facilitates the analyses of option exercise policies in terms of the bond issuer's asset value and interest rate. A detailed review of convertible bond pricing models can be found in Batten et al (2014), Kwok (2014), and Batten et al (2018). 5 According to data collected by Grundy and Verwijmeren (2018), a majority of convertible bonds issued before 2000 are callable; noncallable convertible issues became popular after 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Game options have proved to be important not only in their own right, but also because they underpin the theory for other traded derivatives such as convertible bonds or callable options; see e.g. Kallsen and Kühn [KalKuh05], Kühn and Kyprianou [KuhKyp07], Bielecki et al [Bie08], Wang and Jin [WanJin09], or Kwok [Kwo14].…”
Section: Introductionmentioning
confidence: 99%